Optogenetic protein clustering through fluorescent protein tagging and extension of CRY2 - Hyerim Park (Nature Portfolio, 2017)
Cryptochrome 2 (CRY2) from A. thaliana can be used to control light-dependent protein homo-oligomerization, but the molecular mechanism of CRY2 clustering is not known, limiting its application. Here the authors identify determinants of CRY2 clustering and engineer fusion partners to modulate clustering efficiency.